New copolymers as hosts of ribosomal RNA - Magali Hernández (BMC Chemistry, 2019)
Abstract Functionalized copolymers were synthesized and are proposed as hosts of RNA. The copolymers are based on carboxymethyl cellulose and poly-(ethylene glycol)-OH. These copolymers were functionalized with two amino acids, either lysine or histidine, through amide bond formation. The functionalized copolymer was then used to adsorb ribosomal RNA. The RNA loading was based on the nature of the amino acid functionalization of the copolymer. The array of RNA-copolymers was observed to be soft sphere-like, where the density of spheres was a function of the molecular weight of the carboxymethyl cellulose and the nature of the amino acid. Such RNA-copolymer systems are very sensitive to changes in pH.